2011
DOI: 10.1007/s00784-011-0565-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of a one-step self-etch adhesive in non-carious cervical lesions at 2 years

Abstract: A 2-year randomized, controlled prospective study evaluated the clinical effectiveness of a one-step self-etch adhesive and a "gold-standard" three-step etch-and-rinse adhesive in non-carious Class-V lesions. The null hypothesis tested was that the one-step self-etch adhesive does perform clinically equally well as the three-step etch-and-rinse adhesive. A total of 161 lesions in 26 patients were restored with Clearfil AP-X (Kuraray). The restorations were bonded either with the "all-in-one" adhesive Clearfil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 37 publications
(58 reference statements)
6
25
1
Order By: Relevance
“…However, the authors mentioned that these defects are clinically acceptable because they did not require intervention and could be easily removed by refinishing and repolishing. At the dentin margin, the adhesives behaved equally, in agreement with our study (12).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the authors mentioned that these defects are clinically acceptable because they did not require intervention and could be easily removed by refinishing and repolishing. At the dentin margin, the adhesives behaved equally, in agreement with our study (12).…”
Section: Discussionsupporting
confidence: 92%
“…Adper Easy One (pH ≈ 3.5) is an "ultramild" self-etch adhesive that only superficially interacts with enamel (12), which explains the lower bond strength values for specimens bonded with this material. Also for this group, all failure modes were classified as adhesive failures, confirming the poor performance of this adhesive system when bonded to enamel.…”
Section: Discussionmentioning
confidence: 99%
“…20 Corroborating the current results, Zhou and others 24 and Brackett and others, 21 at one-year and two-year recalls, respectively, evaluated the clinical performance of two-bottle and one-bottle self-etching adhesives and observed no statistically significant differences between the systems. Van Landuyt and others 23 and Ermis and others, 22 after one-year and two-year clinical evaluations, respectively, found that a one-step self-etch adhesive and a three-step etch-and-rinse adhesive were equally clinically successful. Fron and others 1 observed that the effectiveness of a one-step self-etch adhesive was very good after two years of clinical service.…”
Section: Discussionmentioning
confidence: 93%
“…9,10 However, the current results showed good clinical performance of 1-SEAs compared with a 2-ERA, as also observed by Van Landuyt and others 23 and Ermis and others. 22 At the one-year recall, alpha scores for marginal integrity were 97.0% for restorations bonded with Single Bond 2. At the two-year recall, alpha scores for marginal integrity (marginal adaptation) were 97.5% for restorations bonded with Single Bond 2, Clearfil S3 Bond, and Optibond All-in-One.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation